Short Communication: An insight into protein sequences of PTPlike cysteine phytases - VINOD KUMAR; SANJEEV AGRAWAL (Nusantara Bioscience, 2014)
Abstract. Kumar V, Agrawal S. 2014. An insight into protein sequences of PTP-like cysteine phytases. Nusantara Bioscience 6: 102-106. Protein tyrosine phosphatase-like cysteine phytases (CPhy) are novel phytases reported in the ruminant microbial community and suggested to play major role in phytate-phosphorus hydrolysis in animal feed. These phytases are very promising to be used in animal feed applications for monogastric animals. Present study deals with utilization of sequence information of 40 CPhy reference protein sequences for their sequential characterization for conserved regions, phylogenetic relationship, biochemical features, superfamily and functional motifs therein. The study reveals that CPhy, not well-characterized class of phytases, contains conserved sequence feature which may be important catalytic residues. Five major clusters observed in phylogenetic tree with Clostridium sp. as largest cluster. Reported motifs might be used for diversity and expression analysis of CPhy enzymes.